Biomass production and phenology of selected aerobic rice inter cropped with legume cover crop Arachis pintoi / Wafa Mohd Salleh - Mohd Salleh, Wafa (Faculty of Plantation and Agrotechnology, 2015)
Rice is important to Malaysia because it is staple food for this country and mostly of the paddy farmer in Malaysia is a smallholder in total 296 000 of farmers that cultivate a wet land paddy. Aerobic rice is a rice that grown in well-drained, non-puddled and non-saturated soils compare to conventional wetland paddy have a major problem that is weed because the absent of puddled and saturated in the field. Arachis pintoi or pinto peanut is one of leguminous family can increases soil conservation and improvement by fixing nitrogen. In the practice there is no specification of fertilizer application practice in paddy cultivation, only as references. The study is to evaluate the biomass production and phenology of aerobic rice grown intercropping with Arachis pintoi under various rate of fertilizer and determine the relative contribution of nitrogen from Arachis pintoi to total nitrogen uptake of aerobic rice with the difference treatment such as 100% NPK, Arachis pintoi, 50% NPK + Arachis pintoi and 100% NPK + Arachis pintoi. From this study, there is no significant difference (P>0.05) between the treatment of application of fertilizer and intercropping of Arachis pintoi in the aerobic cultivation.